2018
DOI: 10.3390/toxins10110478
|View full text |Cite
|
Sign up to set email alerts
|

The Cyanotoxin BMAA Induces Heterocyst Specific Gene Expression in Anabaena sp. PCC 7120 under Repressive Conditions

Abstract: Cyanobacteria synthesize neurotoxic β-N-methylamino-l-alanine (BMAA). The roles of this non-protein amino acid in cyanobacterial cells are insufficiently studied. During diazotrophic growth, filamentous cyanobacteria form single differentiated cells, called heterocysts, which are separated by approximately 12–15 vegetative cells. When combined nitrogen is available, heterocyst formation is blocked and cyanobacterial filaments contain only vegetative cells. In the present study, we discovered that exogenous BMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(44 citation statements)
references
References 69 publications
1
43
0
Order By: Relevance
“…In order to test BMAA effect on Nostoc under nitrogen-replete conditions, cyanobacterium was grown in three independent biological replicates in sodium nitrate containing BG11N medium for 48 h in two experimental settings: (1) control samples consisted of cells grown without the BMAA treatment and (2) the treated samples consisted of cells grown with addition of an aqueous solution of BMAA (20 µM), as it was performed earlier [ 22 , 23 ]. The analysis of cyanobacteria samples by using LC-MS/MS methods resulted in the identification of 1567 different proteins of Nostoc ( Supplementary Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to test BMAA effect on Nostoc under nitrogen-replete conditions, cyanobacterium was grown in three independent biological replicates in sodium nitrate containing BG11N medium for 48 h in two experimental settings: (1) control samples consisted of cells grown without the BMAA treatment and (2) the treated samples consisted of cells grown with addition of an aqueous solution of BMAA (20 µM), as it was performed earlier [ 22 , 23 ]. The analysis of cyanobacteria samples by using LC-MS/MS methods resulted in the identification of 1567 different proteins of Nostoc ( Supplementary Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…For that reason, BMAA effects were studied, so far mostly in mammalian models, for review [ 15 ]. Knowledge on the synthesis mechanisms of this neurotoxic non-protein amino acid and on the functional role of BMAA in cyanobacteria cells is still scant [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. There are a few experimental studies dedicated to the notable and specific biological impact of BMAA on nitrogen-fixing filamentous cyanobacterium Nostoc (also known as Anabaena ) sp.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fact is that the biological functions of this diamino acid in nature are still unknown. The few studies conducted on its natural producers have concluded that it interferes with nitrogen metabolism and have hypothesized an allelopathic role for BMAA, a common biological phenomenon by which metabolites produced by some organisms affect certain physiological traits of others (Lage et al, 2016b;Popova et al, 2018). In the case of the BMAA-containing paenilamicins, production of the compound was shown to impact competing bacterial populations in the larval gut thus confirming its allelopathic role (Müller et al, 2014).…”
Section: Resultsmentioning
confidence: 91%